Cardiac Tamponade and Laceration of Right Ventricle in Blunt Thoracic Injury: A Case Report - Simbolon, Prabowo W; Putra, Muhammad A (The New Ropanasuri Journal of Surgery, 2020)
Introduction. Cardiac tamponade caused by blunt thoracic injuries is a rare case with a high mortality rate. Generally, patients with blunt cardiac injury were not survived before they reach the hospital. We present the case of a 50-year-old man was admitted to our emergency department after a motorcycle hit the cart he was pushing on the street, and then the handle hit the chest. He presented with hemodynamically unstable and a bruised on precordial area, then he went into cardiac arrest. Standard CPR was done for 2 minutes, continued with intubation and ROSC. FAST showed fluid in the pericardial sac. After doing pericardiocentesis, an amount of blood about +/- 40 mL was aspirated. A median sternotomy was performed, and lacerations were found in the right ventricle and right ventricle pulmonary junction. Method. Literature searching was done in Proquest, PubMed and ScienceDirect database. The research papers were selected based on exclusion and inclusion criteria and were critically appraised using the tools from PRISMA. Result. Two articles were found to be relevant to the topic. Experimental research was not found; there were only two case-report articles. A median sternotomy was a preferable surgical approach in blunt chest trauma with the presentation of cardiac tamponade with hemodynamically unstable. Conclusion. Prompt diagnosis and definitive operation can be lifesaving in traumatic acute cardiac tamponade caused by blunt chest trauma based on the level of evidence 4. The FAST examination was beneficial in diagnosing cardiac tamponade and pericardiocentesis can be a temporary measure. A median sternotomy was a safe surgical approach in controlling the cardiac injury. The patient was discharged on the fifth post-operation day.